The Sensitivity of Animal Cells Sensitized With Bilirubin under Irradiation of Blue and Green Spectral Range - Kozlenkova, O. A.; Plavskaya, L. G.; Mikulich, A. V.; Leusenko, I. A.; Tretyakova, A. I.; Plavskii, V. Yu; Gao, J.; Xiong, D.; Wu, X. (Communications in Physics, 2017)
It has been shown that exposure to radiation of LED sources of light with an emission band maximum at about 465 and 520 nm having substantially identical damaging effects on animal cells in culture, that are in a logarithmic growth phase and preincubated with pigment. Photobiological effect is caused by photodynamic processes involving singlet oxygen generated by triplet excited sensitizer. Mono-exponential type dependence of cell survival on the energy dose indicates that it is bilirubin that acts as a sensitizer but not its photoproducts. The inclusion of bilirubin in the cells, where it is primarily localized in the mitochondria cells, it is accompanied by multiple amplification photochemical stability compared to pigment molecules bound with albumin.